PERAN AUTENTISITAS TERHADAP MINAT BERKUNJUNG KEMBALI KE ANJUNGAN JAWA TENGAH TMII - Saniah, Hothizatus; Novarlia, Irena; Sukirman, Oman (STAH Dharma Sentana Sulawesi Tengah, 2024)
Authenticity is an important role that is able to attract visitors who are looking for an authentic experience. Authenticity will not only attract more visitors but also encourage them to return. The TMII Central Java Pavilion is one of the Regional Pavilions in Taman Mini Indonesia Indah (TMII). The purpose of this study is to find out how the Central Java TMII Pavilion is described and how the role of Authenticity in the interest of visiting the TMII Central Java Pavilion is revisited. In this study, the author uses a quantitative research method with a survey technique design through a questionnaire. Data collection in this study uses observation techniques, interviews, literature studies and documentation. From the results of the research, it was obtained that Authenticity has a very significant role in revisiting.